KAJIAN RESAPAN DAERAH BANDUNG UTARA - Wibowo, M.Joko
Abstract: Northern Bandung area is considered as groundwater recharge area for Bandung Basin. Condition of the area, with various lithology, soil property, land coverage, and slope, will influence infiltration rate. The purpose of this research is to study groundwater infiltration characteristic in order to know correlation between final infiltration rate with lithologic distribution, soil property, slope, and land coverage in this area. Infiltration rate measurement was done with double ring infrltrometer and calculation of the final infiltration rate by using Phillip Method (1957). Correlation between dependent variables (slope, land coverage, % clay. % silt, %o sand, porosity, and sand thickness) with independent variable (final infiltration rate) is analysed statistically with Multiple Linear Regression. Additionally, the correlation of each variable with final infiltration rate is analysed with simple regression , linearly as well as non-linearly. The results show variation of final infiltration rate values in one lithologic unit. In Sandy Tuff lithologic unit the value ranges from 0.05 to 0.84 cm/min, while in Undifferentiated Volcanic Product lithologic unit it ranges from 0.15 to 4.53 cm/min. Multiple linear equations resulting from regression analysis for group of Data I, Data II, and from Sandy Tuff lithologic unit have R > 0.8, which means that they can be used to predict final infiltration rate in the research area. The values of determinant coeficient (R2) resulting from regression analysis are less than one or 100 %, which means that the final infiltration rate is not only determined by land coverage, slope, % clay, % silt, % sand, porosity, and sand thickness. Result of simple linear regression analysis shows that sand thickness has the best correlation among the variables with respect to final infiltration rate, linearly as well as non-linearly. Raising the equation exponent (two, three, and four) in the simple regression does not result in significant change compared with linear equation.